Diamond as a high pressure gauge up to 2.7 Mbar - Dubrovinskaia, Natalia; Dubrovinsky, Leonid; Caracas, Razvan; Hanfland, Michael (Applied physics letters, 2010)
A pressure gauge is a key issue of any high pressure experiment in a diamond anvil cell (DAC). Here we present a method of in situ synthesis of microcrystals of diamond that can be further used as a pressure standard in the course of the same DAC experiment. Calibration curve of the Raman shift versus pressure is extended up to 270 GPa and experimental results are compared with those of ab initio calculations.